Fatigue behavior evaluation in Fe-20Mn-3Al-0.9C alloys by dynamic nanoindetation - Castañeda Villalba, Jaime Andres; Rodriguez Pulecio, Sara Aida (Ingeniería Solidaria, 2023)
Introduction: The article is the product research “New Fe-Mn-Al-C alloys as a potential replacement for conven-tional steels used in the national industry” developed at the Universidad del Valle in the year 2022.Problem: The behavior under cyclic loads in individual grains in Fe-Mn-Al-C steels considering load control and displacement control has been poorly reported due to the complexity and variety of deformation mechanisms present.Objective: To determine the response to fatigue by applying cyclic loads on individual grains by means of monotonic and cyclic nanoindentation to analyze the response on load and displacement control in an auste-nitic Fe-20Mn-3Al-09C alloy.Method: The tests were carried out with a Berkovich indenter at a maximum load of 100 mN (or depth of 1 μm) and unloading 10% of the maximum load (or 95% of maximum depth), for a total of 100 cycles. The behavior of the material to cycles would require evaluating properties such as hardness, modulus of elasticity and contact stiffness, through the analysis of load-unload curves (P-h).Results: The analysis showed that properties such as E and H decrease with increasing cycles due to the activation of deformation mechanisms. These values of E and H for monotonic loads in load control appeared values close to those reported in the literature, while, in displacement control, the values were lower.Conclusions: In load and displacement control, the first two cycles lack of overlap between unloading and loading between cycles, due to a large irreversible plastic deformation and low elastic recovery after unloading. In the subsequent cycles, the overlaps between the hysteresis curves were predominant, as a consequence of the activation of the deformation mechanisms.Study limitation: Activation of deformation mechanisms was not verified.
Keywords: cycle indentation; Fe-Mn-Al-C alloy; softening; nano-fatigue